Transfer of Learning of Business Writing Skills in a Private Organization in Malaysia - Wahidin, Jalilah (2008)
The study examines transfer of learning, determines the catalysts and barriers to transfer and identifies the learning transfer factors such as trainee characteristics, ability, motivation, work environment and personality that contribute to transfer of learning in the context of Corporation X. Transfer of learning was measured five months after the trainees attended a training program entitled the ‘Business Writing Skills Workshop’. Holton, Bates and Ruona’s (2000) Learning Transfer System Inventory (LTSI) scales and Goldberg’s (1999) International Personality Inventory (IPIP) scales were used to determine the catalysts, barriers and transfer factors. The LTSI and IPIP questionnaires were administered and collected during and at the end of the training program. Transfer of learning was measured using retrospective pretest methodology. Data were gathered from 110 executives working in Corporate X. In determining the catalysts and barriers to transfer, the trainees’ responses to the 16 LTSI variables indicated that 10 variables were catalysts and six (6) were barriers. Among the catalysts, the strongest being motivation to transfer and transfer design. All the six (6) variables identified as barriers came from the work environment factor with supervisor sanctions being the most severe. In identifying which transfer factors contributed to transfer of learning, statistically significant relationships existed between transfer design and opportunity to use learning and transfer of learning. Statistical significance was not found in the relationship between IPIP personality traits and transfer of learning. The study found that the trainees transferred 42% of the knowledge and skills learned in the training to their jobs. This study suggested that transfer of learning was influenced by motivation to transfer learning, transfer design, and opportunity to use learning. This result indicated that although work environment was passive, the individuals still made the final decision to transfer the learning. From the finding, it can be inferred that transfer design gave trainees the ability and confidence to transfer the learning back to their job. The presence of opportunity to use learning further enhanced the transfer. Further insights showed that the characteristics of the individual that is motivation to transfer learning played a vital role in the learning transfer. This study recommends that Corporation X prepares its managers/supervisors with a fundamental understanding of the importance of their role as leaders, facilitators and role models in the transfer of learning of their staff and institutes improved incentives that recognize and reward staff that transfer learned behaviors to the workplace.